Investigating antibacterial activity of defatted Moringa Oleifera seed extract on selected gram-negative and gram-positive microbes - Idris Oseni, Munirat; Muyibi, Suleyman Aremu; Abdulkarim, Mohd Ismail; Jamal, Parveen; Hamzah, Mohd. Salleh; Jami, Mohammed Saedi (Progress Publishing Company, 2013)
Moringa oleifera seed extracts has been found to possesses antibacterial properties. In this research, the antibacterial property of the defatted seed extract (after oil removal) was investigated against two gram-negative bacterial strains (Escherichia coli, Pseudosomonas aeruginosa) and two gram-positive bacterial strains (Bacillus subtilis, Staphylococcus aureus). Water and 1 Molar salt solution was used to prepare the defatted seed extracts. Susceptibility tests were carried out using the agar well diffusion method. The effect of increase in concentration of the seed extract was investigated and the Minimum Inhibitory Concentration (MIC) as well as Minimum Bactericidal Concentration (MBC) was also carried out. The results obtained showed that the diameter inhibition zone ranges from 13mm to 30mm, increase in the seed extracts showed a corresponding increase in the inhibition of the bacterial strains. The results also revealed that salt extract f the seed showed higher increase in the antibacterial activity of the seed extract against the bacterial strains when compared with the water seed extract. MIC values of defatted water seed extract obtained were 0.39mg/ml, 0.39mg/ml, 0.78mg/ml, and 0.78mg/ml for Escherichia coli, Pseudosomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus respectively and MIC obtained for the salt solution seed extract is 0.78mg/ml, 0.78mg/ml, 0.78mg/ml, 0.78mg/ml for Escherichia coli, Pseudosomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus respectively. The mode of attack of the seed extracts show that it is strongly bactericidal against Escherichia coli, Pseudosomonas aeruginosa and bacteriostatic against Bacillus subtilis, and Staphylococcus aureus Key words: Moringa oleifera; antibacterial property; MIC; MBC